The Effectiveness of Project-Based Learning Assisted by Educational Teaching Aids of Building Blocks on Students' Mathematical Creative Thinking Skills - wati, Lutfi Rahma; Maharani, Hevy Risqi; Ubaidah, Nila; Aminudin, Mohamad (JURNAL PENDIDIKAN MATEMATIKA, 2024)
Abstract. The aim of this research is to examine the effectiveness of a project-based learning model assisted by educational teaching aids, specifically construction blocks, on students' mathematical creative thinking skills. The research method employed is a pre-experimental design with a one-group pretest-posttest approach. The research instruments consist of observation sheets and student essay tests. Data analysis techniques include individual minimum mastery criteria (MMC) achievement tests, classical completeness tests, pretest-posttest mean difference tests, and N-gain tests. The individual MMC hypothesis test, using a one-sample t-test, yielded a significant value (2-tailed) of 0.000 < 0.05, indicating that after the project-based learning intervention with construction block educational aids, the MMC exceeded 70. The classical completeness test, utilizing Z statistics, resulted in Z_calculated = 3.560545 ≥ Z_table = 0.6736, demonstrating that the proportion of students meeting the minimum mastery criteria exceeded 75%. Furthermore, the mean difference test showed that students' mathematical creative thinking skills increased from 36.82 to 85.15. Additionally, the N-gain test yielded a score of 0.7675, with a percentage of 76.74%, categorizing it as high and effective. Therefore, project-based learning assisted by educational teaching aids, specifically construction blocks, is effective in enhancing students' mathematical creative thinking skills. Keywords: Construction blocks, students' mathematical creative thinking skills.